THE ESTIMATION OF HUMAN-OPERATOR CYBERNETIC ABILITIES DURING THE IMPACT OF DESTABILIZING FACTORS OF EXTERNAL ENVIRONMENT - Polishchuk, Sergii T.; Bogunenko, Nikolay N. (Proceedings of National Aviation University (archive), 2009)
The method of estimation of human-operator cybernetics abilities during of the impacting of destabilizing factors of external environment is suggested. It was proved that up-to-date biomedical approach for periodical health examination of pilots in civil aviation isn’t guarantees theirs cybernetics abilities in cases of influence of destabilizing factors.